Acting to understand and understanding to act. Issue 9 (28th October 2014) - Glanville, Ranulph
Abstract : Purpose: – To establish the essential centrality of a circular relationship between acting and understanding, and a role learning plays in this circularity, with special reference to Aristotle's phronesis and sophia. The purpose of this paper is to establish a position. Design/methodology/approach: – The argument is made through critical, cybernetic analysis and argument. Findings: – The argument reconceptualises key relationships in the approach to understanding the world, and in education. Research limitations/implications: – Research implications are not explored: the argument attempts to lay groundwork for other and later work. Originality/value: – The argument establishes a cybernetic circular causality to replace the currently preferred linear causality.